2020
DOI: 10.1177/0309364620958526
|View full text |Cite
|
Sign up to set email alerts
|

The comprehensive lower limb amputee socket survey: Reliability and validity of the persian version

Abstract: Background: The Comprehensive Lower limb Amputee Socket Survey (CLASS) is a self-reported measure developed to assess prosthetic socket fit in individuals with lower limb amputation. Objective: To assess the reliability and validity of the Persian version of the CLASS. Study Design: Cross-sectional and repeated-measures. Methods: We evaluated the translation and back translation of the CLASS and made the required changes according to expert committee feedback. Then, we recruited 124 participants with unilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…A study on the importance of prosthetic socket fit in individuals with lower‐limb amputation showed that the overall satisfaction of participants in stability, suspension, comfort, and appearance of the socket was 70.1%, 70.54%, 69.21%, and 58.13%, respectively 8 . It is interesting to note that in all four domains of CLASS, the studied patient was more satisfied with socket B. Rouhani et al showed that satisfaction was 69.21% with the socket comfort in 124 individuals with lower‐limb amputation, 8 a bit higher than that of our patient with socket A (62%). However, while using socket B, the level of comfort was 100%, showing a significant increase compared to socket A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study on the importance of prosthetic socket fit in individuals with lower‐limb amputation showed that the overall satisfaction of participants in stability, suspension, comfort, and appearance of the socket was 70.1%, 70.54%, 69.21%, and 58.13%, respectively 8 . It is interesting to note that in all four domains of CLASS, the studied patient was more satisfied with socket B. Rouhani et al showed that satisfaction was 69.21% with the socket comfort in 124 individuals with lower‐limb amputation, 8 a bit higher than that of our patient with socket A (62%). However, while using socket B, the level of comfort was 100%, showing a significant increase compared to socket A.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the prosthetic socket satisfaction, the patient was asked to fill out the Persian version of the Comprehensive Lower‐limb Amputee Socket Survey (CLASS). 8 This questionnaire consists of 15 items in four domains of stability, suspension, comfort, and appearance. In this questionnaire, the prosthetic socket fit was evaluated while the patient was sitting, walking, going up stairs, and wearing tight pants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher score corresponds to less perceived sweat on the skin. The Comprehensive Lower Limb Amputee Socket Survey (CLASS) is a self-report measure of prosthetic socket satisfaction that quantifies suspension, stability, comfort 19 . The scale is 1–4, from strongly disagree to strongly agree, 0 is not applicable.…”
Section: Methodsmentioning
confidence: 99%
“…12 The heterogeneity of intervention, study population, and outcome measures make metaanalysis impossible. 3,12,14,15 The TF socket interface, considered the most important part of the prosthesis, allows the user to control the prosthesis and provides pelvic stabilization during loading. The ischial ramus containment (IRC) socket claims to feature a "bony lock" believed to be most effective during full stance phase.…”
Section: Introductionmentioning
confidence: 99%